Docking and molecular dynamics studies of peripheral site ligand-oximes as reactivators of sarin-inhibited human acetylcholinesterase - de Almeida, Joyce S F D; Cuya Guizado, Teobaldo R; Guimarães, Ana P; Ramalho, Teodorico C; Gonçalves, Arlan S; de Koning, Martijn C; França, Tanos C C (Journal of biomolecular structure & dynamics, 2016)
In the present work, we performed docking and molecular dynamics simulations studies on two groups of long-tailored oximes designed as peripheral site binders of acetylcholinesterase (AChE) and potential penetrators on the blood brain barrier. Our studies permitted to determine how the tails anchor in the peripheral site of sarin-inhibited human AChE, and which aminoacids are important to their stabilization. Also the energy values obtained in the docking studies corroborated quite well with the experimental results obtained before for these oximes.
Keywords: molekulární konformace; Ligands; vodíková vazba; oximy; Molecular Conformation; Humans; nerve agents; ligandy; simulace molekulového dockingu; Oximes; Protein Binding; Molecular Docking Simulation; oximes; peripheral site; acetylcholinesterase; vazebná místa; lidé; Binding Sites; simulace molekulární dynamiky; sarin; Molecular Dynamics Simulation; Acetylcholinesterase; reactivation; vazba proteinů; Hydrogen Bonding; Sarin; acetylcholinesterasa